The Influence of Digital and Environmental Literacy on Greenwashing Skepticism and ESG Report Credibility Among Generation Z University Students in Greater Bandung - Khairunnisa, Adinda Fiona; Siregar, Ifan Wicaksana (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examines how digital literacy and environmental literacy influence greenwashing skepticism and perceptions of the credibility of ESG reports among Generation Z in the Greater Bandung area. This study applies a quantitative design using survey data from 267 respondents, which is examined through a Structural Equation Model-Partial Least Squares (SEM-PLS) approach. The results show that digital literacy and environmental literacy significantly increase skepticism towards greenwashing, but have a negative impact on the perceived credibility of ESG reports. In addition, skepticism towards greenwashing has a negative impact on report credibility and serves as a mediator in the relationship between the two variables of competence and report credibility. This model meets all criteria related to reliability, validity, and appropriateness. These findings highlights the importance of media literacy and environmental literacy competencies in building critical understanding of sustainability.